Effectiveness of Psychodrama-Based Group Guidance in Reducing Bullying Among Indigenous and Non-Indigenous Students: A Quasi-Experimental Study - Nurhasyifa, Najwa; Harahap, Ade Chita Putri (Journal of Social Work and Science Education, 2025)
This study aims to examine the effectiveness of group guidance services using the psychodrama approach in reducing bullying behavior among native and non-native students at Sultan Iskandar Muda Junior High School. Utilizing a quantitative design with an experimental method, the study involved two groups: an experimental group that received psychodrama interventions and a control group that did not receive any intervention. Data were collected through pre-test and post-test measures to assess bullying behavior. The analysis revealed a significant difference between the pre-test and post-test scores in the experimental group. Before the intervention, 12.5% of students were in the high bullying category and 87.5% in the moderate category. After the intervention, 100% of students were in the low category. The Wilcoxon test showed a significant difference (p < 0.05), indicating that the observed changes were not due to chance. The psychodrama intervention in this study involved various techniques such as role playing, role reversal, and empathy training, which enabled students to understand others’ perspectives, including those from different cultural backgrounds. This approach intentionally integrated cultural inclusiveness and intergroup empathy to create a safe and supportive space for all students. These findings suggest that psychodrama is not only effective in reducing bullying behavior but also holds potential as a relevant intervention strategy in multicultural education, as it promotes cross-cultural understanding and strengthens social harmony within the school environment.